The Impact of Chinese Capitalist Business on Indonesia’s Economic Policy and Leadership - muhammad Sakur (Utan Kayu Publishing, 2025)
This study examines the roots of Chinese capitalist business in Indonesia, which has expanded significantly over the past two decades through increased foreign direct investment (FDI) and bilateral trade. It highlights the historical, economic, and political factors shaping this dynamic, while analyzing the Indonesian government's role in managing the influx of Chinese investment using a qualitative-descriptive approach. The findings indicate that China’s economic involvement in Indonesia has deep historical roots, dating back to the colonial era, continuing through the post-independence period, and intensifying under China’s